Differences in Nanosecond Laser Ablation and Deposition of Tungsten, Boron, and WB2/B Composite due to Optical Properties - Tomasz Moscicki (International Journal of Optics)
The first attempt to the deposition of WB3 films using nanosecond Nd:YAG laser demonstrated that deposited coatings are superhard. However, they have very high roughness. The deposited films consisted mainly of droplets. Therefore, in the present work, the explanation of this phenomenon is conducted. The interaction of Nd:YAG nanosecond laser pulse with tungsten, boron, and WB2/B target during ablation is investigated. The studies show the fundamental differences in ablation of those materials. The ablation of tungsten is thermal and occurs due to only evaporation. In the same conditions, during ablation of boron, the phase explosion and/or fragmentation due to recoil pressure is observed. The deposited films have a significant contribution of big debris with irregular shape. In the case of WB2/B composite, ablation is significantly different. The ablation seems to be the detonation in the liquid phase. The deposition mechanism is related mainly to the mechanical transport of the target material in the form of droplets, while the gaseous phase plays marginal role. The main origin of differences is optical properties of studied materials. A method estimating phase explosion occurrence based on material data such as critical temperature, thermal diffusivity, and optical properties is shown. Moreover, the effect of laser wavelength on the ablation process and the quality of the deposited films is discussed.